Grupo Espanca!: arranjos poéticos para uma cena contemporânea - Amâncio, Aryadne Cristiny de Oliveira (2012)
This research discusses the mining group by Espanca! On his shows Por Elise, Amores Surdos and Congresso Internacional do Medo and a contemporary fear that elements of the word, space and time are arranged so as to bring the breakdown voltage and appropriation of the concepts of modern theater. With the research work focused on the Espanca! can be analyzed using these elements and how they may reveal ways to build a poetry linked to change in time and the identity element for the theater group. The research reveals the creation of the remains of a group that deals with contemporary thinking as the driving force of appropriation for the poetic and arrangements related to the process of creating and stimulating ways to explore theatrical language and speech implicit in the narrative. The word, space and time in this context are reconfigured as a way to provide a communication that reveals the poetic discourse of the group and can support the desires of the world speaking and thinking to society. The works reveal a building built with the reflections of contemporary theatrical field, but deeply marked by the appropriation of elements of the modern theater and proposals, singling out a work that evokes the same time as the transgressions of narrative fragmentation and no linearity seek to align them to the concept presence and striking against the classical theater.